Application value of weight-adjusted waist circumference index and cardiometabolic index in hypertensive patients with albuminuria: results from the National Health and Nutrition Examination Survey 2005–2020 - Yulu Yang; Jianwu Huang; Jiacheng Wu; Xuehan Li; Yalei Wang; Hao Chen; Zhihua Qiu; Zihua Zhou (Renal Failure)
Background The Weight-adjusted Waist Index (WWI) and Cardiometabolic Index (CMI) are novel metrics developed to evaluate visceral fat distribution and metabolic health. This study aimed to explore the associations between these indices and albuminuria in hypertensive patients.Methods We conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES), obtained between 2005 and 2020. Multivariate logistic regression models, generalized additive models, and smooth curve fitting were employed to examine the relationships between WWI, CMI, and albuminuria. Nonlinear associations were further investigated using a piecewise linear model to identify inflection points. Subgroup analyses were performed, and the diagnostic performance of these indices was evaluated using Receiver Operating Characteristic (ROC) curves.Results After adjusting for potential confounders, both WWI and CMI were significantly associated with increased odds of albuminuria (OR = 1.37 and 1.09, respectively). The relationship between WWI and urinary albumin-creatinine ratio (UACR) exhibited a nonlinear pattern, with an inflection point at 11.65. For WWI values lower than 11.65, significant correlations were observed. Subgroup analysis revealed a stronger association between WWI and albuminuria in males. ROC curve analysis indicated that WWI outperformed CMI in detecting albuminuria, with CMI showing slightly lower diagnostic accuracy. When combined with other clinical indicators, the integrated area under the curve (AUC) reached 0.732.Conclusion Both WWI and CMI demonstrated significant associations with albuminuria in hypertensive patients, highlighting their potential utility in disease screening. Clinical attention should be directed toward individuals with WWI below 11.65, particularly male subjects, as this threshold was associated with significantly increased prevalence of albuminuria.